Raman spectroscopy as a tool for monitoring mesoscale continuous-flow organic synthesis: Equipment interface and assessment in four medicinally-relevant reactions - Hamlin, Trevor A.; Leadbeater, Nicholas E. (Beilstein Journal of Organic Chemistry, 2013)
An apparatus is reported for real-time Raman monitoring of reactions performed using continuous-flow processing. Its capability is assessed by studying four reactions, all involving formation of products bearing α,β-unsaturated carbonyl moieties; synthesis of 3-acetylcoumarin, Knoevenagel and Claisen–Schmidt condensations, and a Biginelli reaction. In each case it is possible to monitor the reactions and also in one case, by means of a calibration curve, determine product conversion from Raman spectral data as corroborated by data obtained using NMR spectroscopy.
Keywords: flow processing; Raman spectroscopy; reaction monitoring; α,β-unsaturated carbonyl

Micro Reaction Technology in Organic Synthesis - Wiles, C.; Watts, P. (CRC Press, 2011)

Chemical Reactions and Processes under Flow Conditions - Luis, S. V.; Garcia-Verdugo, E. (Royal Society of Chemistry, 2010)

(untitled) - Wiles, C.; Watts, P. (Chem. Commun., 2011)

(untitled) - Wegner, J.; Ceylan, S.; Kirschning, A. (Chem. Commun., 2011)

(untitled) - Razzaq, T.; Kappe, C. O. (Chem.–Asian J., 2010)

(untitled) - Mark, D.; Haeberle, S.; Roth, G.; von Stetten, F.; Zengerle, R. (Chem. Soc. Rev., 2010)

(untitled) - van den Broek, S. A. M. W.; Leliveld, J. R.; Delville, M. M. E.; Nieuwland, P. J.; Koch, K.; Rutjes, F. L. J. T. (Org. Process Res. Dev., 2012)

(untitled) - Baxendale, I. R. (J. Chem. Technol. Biotechnol., 2013)

(untitled) - Malet-Sanz, L.; Susanne, F. (J. Med. Chem., 2012)

(untitled) - McMullen, J. P.; Jensen, K. F. (Annu. Rev. Anal. Chem., 2010)

(untitled) - Moore, J. S.; Jensen, K. F. (Org. Process Res. Dev., 2012)

(untitled) - Prim, D.; Crelier, S.; Segura, J.-M. (Chimia, 2011)

(untitled) - Greener, J.; Abbasi, B.; Kumacheva, E. (Lab Chip, 2010)

(untitled) - Steinfeldt, N.; Bentrup, U.; Jähnisch, K. (Ind. Eng. Chem. Res., 2010)

(untitled) - Floyd, T. M.; Schmidt, M. A.; Jensen, K. F. (Ind. Eng. Chem. Res., 2005)

(untitled) - Ferstl, W.; Klahn, T.; Schweikert, W.; Billeb, G.; Schwarzer, M.; Loebbecke, S. (Chem. Eng. Technol., 2007)

(untitled) - Benito-Lopez, F.; Verboom, W.; Kakuta, M.; Gardeniers, J. G. E.; Egberink, R. J. M.; Oosterbroek, E. R.; van den Berg, A.; Reinhoudt, D. N. (Chem. Commun., 2005)

(untitled) - Lu, H.; Schmidt, M. A.; Jensen, K. F. (Lab Chip, 2001)

(untitled) - Gökay, O.; Albert, K. (Anal. Bioanal. Chem., 2012)

(untitled) - Jones, C. J.; Larive, C. K. (Anal. Bioanal. Chem., 2012)

(untitled) - Mozharov, S.; Nordon, A.; Littlejohn, D.; Wiles, C.; Watts, P.; Dallin, P.; Girkin, J. M. (J. Am. Chem. Soc., 2011)

(untitled) - Rinke, G.; Ewinger, A.; Kerschbaum, S.; Rinke, M. (Microfluid. Nanofluid., 2011)

(untitled) - Leung, S. A.; Winkle, R. F.; Wootton, R. C. R.; deMello, A. J. (Analyst, 2005)

(untitled) - Lee, M.; Lee, J.-P.; Rhee, H.; Choo, J.; Chai, Y. G.; Lee, E. K. (J. Raman Spectrosc., 2003)

(untitled) - Fletcher, P. D. I.; Haswell, S. J.; Zhang, X. (Electrophoresis, 2003)

(untitled) - Browne, D. L.; Wright, S.; Deadman, B. J.; Dunnage, S.; Baxendale, I. R.; Turner, R. M.; Ley, S. V. (Rapid Comm. Mass. Spectrosc., 2012)

(untitled) - Koster, S.; Verpoorte, E. (Lab Chip, 2007)

(untitled) - Carter, C. F.; Lange, H.; Ley, S. V.; Baxendale, I. R.; Wittkamp, B.; Goode, J. G.; Gaunt, N. L. (Org. Process Res. Dev., 2010)

(untitled) - Brodmann, T.; Koos, P.; Metzger, A.; Knochel, P.; Ley, S. V. (Org. Process Res. Dev., 2012)

(untitled) - Rueping, M.; Bootwicha, T.; Sugiono, E. (Beilstein J. Org. Chem., 2012)

Microwaves in Organic Synthesis - Leadbeater, N. E.; Schmink, J. R.; Hamlin, T. A. (Wiley-VCH, 2012)

(untitled) - Leadbeater, N. E.; Schmink, J. R. (Nat. Protoc., 2008)

(untitled) - Leadbeater, N. E.; Smith, R. J.; Barnard, T. M. (Org. Biomol. Chem., 2007)

(untitled) - Leadbeater, N. E.; Smith, R. J. (Org. Lett., 2006)

(untitled) - Leadbeater, N. E.; Smith, R. J. (Org. Biomol. Chem., 2007)

(untitled) - Schmink, J. R.; Holcomb, J. L.; Leadbeater, N. E. (Chem.–Eur. J., 2008)

(untitled) - Schmink, J. R.; Holcomb, J. L.; Leadbeater, N. E. (Org. Lett., 2009)

(untitled) - Chaplain, G.; Haswell, S. J.; Fletcher, P. D. I.; Kelly, S. M.; Mansfield, A. (Aust. J. Chem., 2013)

(untitled) - Kelly, C. B.; Lee, C.; Leadbeater, N. E. (Tetrahedron Lett., 2011)

Gaussian 09, Revision A.02 (Gaussian, Inc., 2009)

(untitled) - Batovska, D. I.; Todorova, I. T. (Curr. Clin. Pharmacol., 2010)

(untitled) - Bowman, M. D.; Jacobson, M. M.; Blackwell, H. E. (Org. Lett., 2006)

(untitled) - Singh, K.; Singh, K. (Adv. Heterocycl. Chem., 2012)

(untitled) - Panda, S. S.; Khanna, P.; Khanna, L. (Curr. Org. Chem., 2012)

(untitled) - Kappe, C. O. (QSAR Comb. Sci., 2003)

(untitled) - Mukhopadhyay, C.; Datta, A.; Banik, B. K. (J. Heterocycl. Chem., 2011)

(untitled) - Fang, Z.; Lam, Y. (Tetrahedron, 2011)

(untitled) - Dallinger, D.; Kappe, C. O. (Nat. Protoc., 2007)

(untitled) - Singh, K.; Arora, D.; Singh, K.; Singh, S. (Mini-Rev. Med. Chem., 2009)

(untitled) - Kappe, C. O. (Eur. J. Med. Chem., 2000)

(untitled) - Pagano, N.; Herath, A.; Cosford, N. D. P. (J. Flow Chem., 2011)

(untitled) - Prosa, N.; Turgis, R.; Piccardi, R.; Scherrmann, M.-C. (Eur. J. Org. Chem., 2012)

(untitled) - Ravikumar, I.; Saha, S.; Ghosh, P. (Chem. Commun., 2011)

(untitled) - Li, Z.-N.; Chen, X.-L.; Fu, Y.-J.; Wang, W.; Luo, M. (Res. Chem. Intermed., 2012)

(untitled) - Stroba, A.; Schaeffer, F.; Hindie, V.; Lopez-Garcia, L.; Adrian, I.; Froehner, W.; Hartmann, R. W.; Biondi, R. M.; Engel, M. (J. Med. Chem., 2009)

(untitled) - Wijnberg, H.; Vries, T. R.; Pouwer, K.; Nieuwenhuijzen, J. (3-Oxopropane-1-sulphonic acids and sulphonates, 2003)

(untitled) - Xu, D.-Z.; Li, H.; Wang, Y. (Tetrahedron, 2012)